Lepiota cholistanensis a new species of Lepiota (Agaricaceae: Basidiomycota) from Cholistan desert, Pakistan - Bashir, Hira; Usman, Muhammad; Khalid, Abdul Nasir (Phytotaxa, 2020)
Lepiota cholistanensis was collected from an unusual locality of Cholistan desert, an unexplored area of Pakistan. This species is characterized by having small basidiomata provided with slightly uplifted brown squamules on pileus surface. Stipe color changes to brown on handling or bruising. Compact hymeniderm pileus covering containing variable shaped pileus elements varies from sub-globose to broadly clavate, long and narrowly clavate, and sphaeropedunculate having cylindrical ante-terminal elements and cheilocystidia are cylindrical to narrowly clavate. Basidiospores are sub-globose, broadly ellipsoid to vaguely oval shaped, olivaceous green, binucleate and non-dextrinoid. The phylogenetic analyses were performed using ITS and LSU datasets. Our newly described taxon grouped well in section Cristatae during the phylogenetic analyses.